2015
DOI: 10.1016/j.jiph.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of antibiotics resistance among uropathogens in Omani children presenting with a single episode of urinary tract infection

Abstract: Urinary tract infection (UTI) is one of the most common community-acquired infections. Different organisms can be the cause of UTI in children, with resistance to antibiotics becoming a significant problem in the choice of treatment. Worldwide studies have documented the prevalence of uropathogens in different countries. However, there is no previous study documenting the incidence of different uropathogens in Oman. We aim to report the most common uropathogens and their antibiotic sensitivity patterns in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 23 publications
10
25
1
Order By: Relevance
“…The bacteriologic profile and resistance patterns of uropathogens found in our study are consistent with the most recently published regional study in children from Oman [3]. E. coli, in particular, accounted for over two-thirds of all UTIs in children, with K. pneumonia e being the second most common uropathogen.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The bacteriologic profile and resistance patterns of uropathogens found in our study are consistent with the most recently published regional study in children from Oman [3]. E. coli, in particular, accounted for over two-thirds of all UTIs in children, with K. pneumonia e being the second most common uropathogen.…”
Section: Discussionsupporting
confidence: 91%
“…Almost half of these two organisms were resistant to co-trimoxazole, and approximately one-third were resistant to amoxicillin/clavulinic acid. In addition, approximately one-quarter of these strains were resistant to cefuroxime [3]. A local study at our institution evaluated the role of renal ultrasound in children with a discharge diagnosis of UTI.…”
Section: Introductionmentioning
confidence: 99%
“…However, our study revealed an overall resistance of 50.4% and E. coli-specific resistance of 49.0% to this antibiotic. Similar results were obtained in a recent study of this nature [21] conducted in the Sultanate of Oman, which revealed an overall resistance of 47% and E. coli-specific resistance of 50% to this antibiotic. This finding is in contrast to reports from European countries of low resistance rates, ranging from 28% to 30% [22,23], and to those from African countries of high resistance rates, ranging from 88.3% to 98.6% [24,25].…”
Section: Discussionsupporting
confidence: 90%
“…]. Moreover, antibiotic resistance can negatively affect both individual patient health and public health (and is considered to be one of the biggest global public health challenges) [ 10 ]. Finally, prolonged hospital stays and extended medical treatment for antibiotic-resistant infections may increase the financial burden [ 11.…”
Section: Assessing Infectious Disease Among Children: the Need For Immentioning
confidence: 99%